GAMBARAN PENGETAHUAN IBU TENTANG MENGKONSUMSI TABLET TAMBAH DARAH PAD TRIMESTER II DAN III DI PMB A DESA KALISUREN KAB BOGOR 5 NOVEMBER - 5 DESEMBER 2020 - Prihantiningsih, Anggarani (Jurnal Ilmiah Bidan (JIB), 2023)
The second trimester of pregnancy is containing an embryo or fetus in the body at 14-28 weeks. At this time pregnant women will feel more calm, peaceful without significant disturbances. In the second trimester the fetus develops towards maturity. Third trimester pregnancy is a pregnancy with the age of 28-40 weeks which is a time to prepare for birth and position as a parent, such as focusing attention on the presence of the baby, so it is also known as the waiting period. Iron (Fe) tablets are mineral tablets needed by the body for the formation of red blood cells or hemoglobin. The element Fe is the most important element for the formation of red blood cells. Iron is naturally obtained from food. If pregnant women lack iron in the diet they consume daily, it can cause nutritional anemia (lack of blood). The purpose of this study was to describe the level of knowledge of pregnant women about consuming blood-added tablets in the second and third trimesters of pregnancy in PMB A. Kalisuren Village, Kab. Bogor for the period 5 November - 5 December 202. The design of this study is a descriptive type of research, from 40 pregnant women who consume blood-added tablets (Fe) based on sufficient knowledge 40%, mothers with less knowledge are 32.5%, while those with low knowledge good that is 27.5%.